Four analysis moments for fuzzy cognitive mapping in participatory research - Iván Sarmiento; Anna Dion; Mateja Šajna; Neil Andersson (Global Health Action)
Fuzzy cognitive mapping (FCM) is a practical tool in participatory research. Its main use is clarifying causal understandings from several knowledge sources. It provides a shared substrate or language for sharing views of causality. This makes it easier for different interest groups to agree what to do next. Each map is a collection of causal relationships with three elements: factors (cause and outcome), arrows linking factors, and weights indicating the perceived influence of each cause on its outcome. Stakeholder maps are soft models of how they see causes of an outcome, such as access to services or systemic racism. Based on a standardized FCM protocol, we present four moments in FCM analysis. (1) Agree shared meaning across maps. (2) Calculate the maximum influence of perceived causes. (3) Simplify the maps for communication. (4) Identify priorities for action. We provide explanations of the four moments in FCM analysis, with examples from five countries. FCM offers a practical means to guide health action. It incorporates local perspectives with transparent and traceable procedures.